Pendaftaran Tanah Sistematis Lengkap Sebagai Dasar Perubahan Sistem Publikasi Pendaftaran Tanah - Bhim Prakoso (Journal of Private and Economic Law, 2021)
Land is a two-dimensional part of the earth in the form of land, which essentially has a dual function for human life. Given the importance of land, the government needs to regulate it in the hope that it can provide welfare, happiness, and certainty to rights owners. With regard to rights, it is necessary to have evidence, namely a certificate issued by the Land Office. The mechanism for issuing certificates by referring to the land registration system with a negative system has a positive tendency, but this system still causes problems in the land sector. Starting from these problems, the government created a complete systematic land registration program (PTSL), with the hope of providing certainty to the community that owns land rights. PTSL can be indicated as a method for changing the land registration system to a positive system. The status of the certificate in the positive system, which is the proof of absolute land rights and the only proof of land rights. The main characteristic of the positive system is that land registration/registration of land rights is guaranteed perfectly because the name registered in the land book is indisputable, even though it turns out that it is not the rightful owner of the land. We must admit that negative systems have a positive tendency to have many weaknesses and therefore need to be ended. And the land registration system in the future shifts to land registration with a positive system, with the aim of creating legal certainty, protecting the interests of land rights holders (certificate), of course, it is mandatory for applicants for rights to be based on and/or based on good faith as well as the correctness of physical and juridical data. KEYWORDS: PTSL, Land Rights, Land Registration System.